PENGARUH KEPEMIMPINAN, MOTIVASI, DAN IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI KARYAWAN PADA PT PRAJA BALI TRANSPORTASI - I Gede Giri Utama Yasa; I Gusti Ngurah Bagus Gunadi; I Wayan Suarjana (VALUES, 2021)
Organizational commitment shows a person's power in identifying their involvement in a part of the organization, built on the basis of workers' belief in organizational values, the willingness of workers to help achieve people's goals, and loyalty to remain a member of the organization. The purpose of this study was to determine and analyze the influence of leadership, motivation and organizational climate on employee organizational commitment at PT Praja Bali Transportasi. The population in this study were all employees of PT Praja Bali Transportasi. The sample in this study were 133 people who were determined using the Slovin formula. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results of the analysis show that partially leadership, motivation, and organizational climate have a positive and significant effect on employee organizational commitment at PT Praja Bali Transportasi.